Mentoring as critically engaged praxis : storying the lives and contributions of Black women administrators - Cobb-Roberts, Deirdre; Esnard, Talia (Contemporary perspectives on the lives of teachers., 2020)
"Black women have historically been marginalized in academia (Turner & Myers, 2000; Turner, 2002; Collins, 2002). While the contemporary landscape of higher education has changed, the number of women and ethnic minorities who serve as higher education administrators (chair, dean, provost, vice president, chancellor, or president) still lags behind (Ross & Green, 2000; Johnson-Bailey & Cervero, 2002; Turner, 2008; Cobb-Roberts & Agosto, 2011/2012). Such underrepresentation of Black women therefore is more than an issue of low numbers; it is also a question of equity (of access commensurate with population numbers), of the extent to which institutional climates support/sustain Black woman administrators, and, of the underutilization of a diverse talent pool. In such contexts, mentoring, networking and transformative leadership practices become critical for the socialization, retention, and progression of marginalized faculty (Johnson-Bailey & Cevero, 2002; McCray, 2011; Lloyd-Jones, 2011, 2014). Where leadership is tied to structures of power (Jean-Marie, 2006; Tran, 2014), mentoring can also can assist African American women faculty and administrators by ''providing access to information networks and opportunities that help them deal with factors critical to their career choices and development'' (Smith & Crawford, 2007, p. 263). As we move to advance the call for more socially just environments, our aim is to generate more pointed discussions around the prospects, possibilities and constraints of mentoring practices that are framed around and operate within an academic context. This edited volume seeks to interrogate the structures of power that potentially affect the structures of power that affect the perceptions, experiences, performance and practices of Black women administrators. The chapters examine the nature and dynamics of the conflict within that space and the ways in which they transcend or confront the intersecting structures of power in academe. A related expectation is for interrogations of the ways in which their institutional contexts, marginalized status, structures of power inform their navigational strategies and leadership practices. More specifically, this work explores mentorship as critical praxis; that being, the ways in which Black women's thinking and practices around mentoring affect their institutional contexts or environment, and, that of other marginalized groups within academe. A discussion of Black women in higher education administration as critically engaged mentors will ultimately diversify thought, approaches, and solutions to larger social and structural challenges embedded within academic climates"--